Family management characteristics in parents of children with retinoblastoma: a latent profile analysis - Zeng, Changjuan; Zhou, Lingling; Wu, Peixia; Zhao, Ting; He, Guanghao; Wang, Hui; Wang, Lin; Jia, Renbing; Hou, Lili (Frontiers in Pediatrics, 2026)
Background and aimThe effective management of a child with cancer by their family depends on their coping strategies, the child's treatment outcomes, and their quality of life. For families of children with retinoblastoma, this study aims to use latent profile analysis to categorize family management patterns, understand their traits, explore influencing factors, and provide a theoretical basis for targeted interventions.MethodsFrom February to April 2024, a cross-sectional study was conducted with the parents of 608 children with retinoblastoma. These parents completed a survey assessing family management, comprehensive needs, coping tendencies, family functioning, social support and levels of depression, anxiety and stress.ResultsThree family management categories were defined as: high-level (n = 93), moderate-level (n = 268), and low-level functioning (n = 247). Multiple logistic regression analysis showed that better family functioning (odds ratio [OR] = 0.821, P = 0.004), unilateral diseased eyes (OR = 0.286, P = 0.001) and high social support (OR = 0.972, P = 0.023) increased the likelihood of high-level functioning group. Factors linked to the low-level family management group included severe depression (OR = 1.320, P = 0.005), severe stress (OR = 1.210, P = 0.033), high comprehensive needs (OR = 1.025, P = 0.001), junior high school and below education (OR = 4.021, P = 0.005).ConclusionsThe family management characteristics of parents of children with retinoblastoma exhibit group heterogeneity, and key factors affecting this heterogeneity have been identified. These include family functioning, comprehensive needs, educational background, depression, stress, and social support. Healthcare professionals can use this information to develop targeted intervention strategies and improve family management.